An updated role of microRNA-124 in central nervous system disorders: a review - Sun, Yang; Luo, Zhu-Min; Guo, Xiu-Ming; Su, Ding-Feng; Liu, Xia (Frontiers in Cellular Neuroscience, 2015)
MicroRNA-124 (miR-124) is the most abundant miRNA in the brain. Biogenesis of miR-124 displays specific temporal and spatial profiles in various cell and tissue types and affects a broad spectrum of biological functions in the central nervous system (CNS). Recently, the link between dysregulation of miR-124 and CNS disorders, such as neurodegeneration, CNS stress, neuroimmune disorders, stroke, and brain tumors, has become evident. Here, we provide an overview of the specific molecular function of miR-124 in the CNS and a revealing insight for the therapeutic potential of miR-124 in the treatment of human CNS diseases.